Deterministic Discrete Fracture Network Model and Its Application in Rock Mass Engineering - Shuangfeng Guo; Runen Qi; Peng Zhang (Applied Sciences)
This study departs from conventional stochastic statistical approaches for rock mass structural modeling. Based on deterministic structural surface parameters, including orientation (dip and dip direction), trace length, trace center coordinates, and spacing between structural surface sets, this research investigates the relationships among volumetric density, areal density, structural surface persistence, and inter-set spacing. With a focus on model domain dimensions, positioning of the model center, and mitigation of boundary effects, the methodology systematically addresses key considerations in modeling joints, layers, and faults. A deterministic Discrete Fracture Network (DFN) modeling approach is proposed accordingly. In this framework, joints are represented by disks, whereas lithological interfaces such as layers and faults are modeled as flat planes. The proposed method was applied to the Qingdao Metro Line 15 project. Validation results demonstrate that the surrounding rock classification derived from the model is in good agreement with field geological investigation data.